(untitled) (Global Journal of Human-Social Science, 2025)
This theoretical and qualitative study addresses the central question of how spirituality morality and ethics articulate as essential dimensions of human formation and fundamental pillars of Integral Education The research aims to demonstrate that spirituality can be conceptualized as a formative and integrating category of knowledge morality and ethics within the educational context The methodology employed is a theoretical synthesis and narrative review of key philosophical and educational literature focusing on the conceptual evolution of these dimensions The analysis is structured around thematic clusters beginning with the systemic perspective of Fritjof Capra which frames spirituality as a unifying dimension of reason ethics and moral consciousness The perspective expressed in the paradigm of wholeness and interconnection a central theme for the thesis of Integral Education finds in Capra a contemporary conceptual lens through which the historical development of this theme is interpreted Subsequently the study traces the historical-philosophical development from classical thought Socrates Plato Aristotle to modern and contemporary perspectives Kant Nietzsche Tillich Bauman culminating in the Latin American and territorial view of Rodolfo Kusch This approach allows for a critical synthesis of how these concepts have shaped the understanding of human formation The main finding is that spirituality understood in its philosophical and educational sense constitutes an ontological and formative dimension of the human being articulating reason morality and ethical sensibility The study concludes that the integration of this dimension into Integral Education expands the horizon of formation offering a specific framework for pedagogical practices that promote dialogue critical consciousness and humanization thereby advancing the existing literature by providing a cohesive conceptual model for its application